Implementasi Psikologi Manajemen dalam Menciptakan Daya Saing Lulusan di Lembaga Pendidikan - Erna Dwi Lestari; Moh. Amin Indra Kusuma; Hilma Fitriatuzzuhria; Achmad Zakaria; Septa Muhammad Royhan; Mu’allimin Mu’allimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Graduates competitiveness is a major factor in determining their readiness to face the increasingly competitive world of work. Management psychology plays an important role in shaping the character, skills, and mentality needed by graduates to be able to adapt to the dynamics of the industry. Through a management psychology approach, such as strengthening leadership, increasing motivation, and managing stress and emotions, graduates can develop a professional and productive attitude. In addition, the application of psychological theory in human resource management allows for the development of soft skills that support work readiness, such as effective communication, teamwork, and problem solving. The application of management psychology in the world of education can be done through various strategies, such as coaching, mentoring, and the formation of an academic culture that is oriented towards self-development. With this approach, educational institutions can create a learning environment that encourages the growth of character and competency of graduates holistically. In addition, the synergy between education and the industrial world is also an important factor in increasing the competitiveness of graduates, where learning based on practice and direct experience can strengthen their readiness to face the challenges of the world of work.